STRATEGI RETENSI KONSUMEN PADA KUALITAS PELAYANAN SEBAGAI KEUNGGULAN BERSAING PADA APOTEK INDAH DI KABUPATEN SIDENRENG RAPPANG - Elzahwa Zakia; Adam Latif; Haslindah; Muhammad Rusdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze customer retention strategies and service quality optimization as competitive advantages at Apotek Indah in Sidenreng Rappang Regency. The study employed a qualitative approach using interviews, observations, and documentation as data collection techniques. The research informants consisted of the pharmacy manager, employees, customers, and surrounding community members selected through purposive sampling. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the customer retention strategy implemented by Apotek Indah is based on customer satisfaction, customer trust, and customer commitment. Customer trust emerged as the most dominant factor in retaining customers, supported by the provision of safe medicines, services tailored to customer needs, and clear and accurate drug information. Furthermore, service quality is optimized through the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy, with reliability being the most dominant dimension. The results indicate that customer retention strategies and service quality mutually reinforce each other in enhancing customer loyalty and creating a sustainable competitive advantage for Apotek Indah amid increasingly intense competition in the pharmacy industry.